Complete chloroplast genome of Lamium takesimese Nakai (Lamiaceae): an endemic species in South Korea - Kyu Tae Park; Jaehang Shin; Seonjoo Park (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome of Lamium takesimense (Lamiaceae), an endemic species in South Korea, are presented in this article. The genome size is 150,626 bp in length, with 38.6% of GC content. It consists a large single-copy (LSC) region (82,527bp) and a small single-copy region (SSC) (17,185bp) which were separated by two inverted repeat (IRs) regions (25,457bp). The complete chloroplast genome contains 111 unique genes, including 77 protein-coding genes, 4 rRNA genes, and 30 tRNA genes.